Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Aksesoris Otomotif Merek Honda Yang Diproduksi Oleh PT Prima Komponen Indonesia Di Kota Tangerang Selatan - Nandya Dwi Putri; Ade Ratna Sari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of product quality and price on purchasing decisions for Honda brand automotive accessories produced by PT Prima Komponen Indonesia Tanggerang Selatan City. The method used was quantitative with a descriptive approach, with a sample of 1,908 respondents, 95,019 0r 95 of whom were selected. Data analysis techniques in this study included multiple linear regression analysis, validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, and hypothesis testing using t-tests and f-tests. The results of this study indicate that product quality influences purchasing decisions. This can be seen from the t-test, with a calculated t-value > t-table (6.798 > 1.986), reinforced by a significance value of 0.000 < 0.05. Price influences purchasing decisions, this can be seen from the t test with t count > t table or (6.276 > 1.986) this is reinforced by a significance value of 0.000 < 0.05. Product quality and price influence purchasing decisions simultaneously, this can be seen from the results of the F test where the calculated F value > F table (33.155) > 3.100) this is also reinforced by a probability significance value of 0.000 < 0.05.